Socio-economic analysis of farmer preferences of fodder legumes attributes and information flow among smallholder dairy farmers in Central Kenya: A case study of Calliandra and Desmodium. - Sinja, J. (University of Nairobi, 2007)
It has been recognized that livestock production can contribute to sustainable livelihoods in the rural areas through increased food and nutritional security and incomes especially for the rural poor in the less developed countries. Low quantities and poor quality basal diet, and lack of high quality protein feeds have been identified as the major constraint to improved milk production in sub-Saharan Africa. In Kenya the problem is compounded by high cost of commercial feeds that are beyond the reach of the smallholder milk producers, resulting in farmers producing only 50% of the potential annual milk production of 4 billion litres. There have been several attempts to introduce fodder legumes in livestock production systems without success in most regions. In Kenya efforts to introduce fodder legumes started more than 2 decades ago but still a very small percentage of farmers have adopted this technology. Previous studies on adoption of these fodders have not embraced the more client-oriented approaches such as farming systems and farmer-participatory research. Much of their research has been driven by a macro-level, constraint oriented analysis that assumes a set of objectives that is not necessarily shared by any livestock producers.